2022
DOI: 10.3390/agronomy12122993
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilisation of an Aspergillus niger Derived Endo-1,4-β-Mannanase, Man26A, on Glutaraldehyde-Activated Chitosan Nanoparticles for the Effective Production of Prebiotic MOS from Soybean Meal

Abstract: An Aspergillus niger endo-1,4-β-mannanase, Man26A, was confirmed by FTIR and XRD to be immobilised on glutaraldehyde-activated chitosan nanoparticles via covalent bonding. The immobilisation (%) and activity yields (%) were 82.25% and 20.75%, respectively. The biochemical properties (pH, temperature optima, and stability) were then comparatively evaluated for both the free and immobilised Man26A. The optimal activity of Man26A shifted to a lower pH after immobilisation (pH 2.0–3.0, from pH 5 for the free enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Other authors who have immobilized β-mannanase have also conducted stability tests, typically for 10 cycles. However, in their studies, they observed a more pronounced decrease in activity compared to what was reported in this work [9,33]. This result demonstrates the effectiveness of the immobilization methodology and the type of support used to retain enzymatic activity.…”
Section: Operational Stabilitysupporting
confidence: 47%
See 2 more Smart Citations
“…Other authors who have immobilized β-mannanase have also conducted stability tests, typically for 10 cycles. However, in their studies, they observed a more pronounced decrease in activity compared to what was reported in this work [9,33]. This result demonstrates the effectiveness of the immobilization methodology and the type of support used to retain enzymatic activity.…”
Section: Operational Stabilitysupporting
confidence: 47%
“…(2022) achieved immobilization on a chitosan particle support and hydrolyzed soybean flour, identifying only mannobiose, reaching a concentration of 350 mg/L [9]. In another study, Chen et al (2023) immobilized mannanases and released 7.94 (g/L) of MOS (M2-M3) from konjac flour after 8 h of hydrolysis [33].…”
Section: Model Verification and Optimal Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment with dilute sodium hydroxide was found to be the most effective method. Finally, Anderson et al [25] report the immobilization of enzymes produced by Aspergillus niger for producing mannooligosaccharides from soybean meal. As a main conclusion, the authors state that the prebiotic potential of soybean meal-produced sugars on the growth and viability of probiotic bacteria is better than that of glucose.…”
Section: This Issuementioning
confidence: 99%